Influence of sub- and super-solar metallicities on the composition of solid planetary building blocks - Bitsch, Bertram; Battistini, Chiara (Astronomy and astrophysics, 2020)
The composition of the protoplanetary disc is thought to be linked to the composition of the host star, where a higher overall metallicity provides the building blocks for planets. However, most of the planet formation simulations only link the stellar iron abundance [Fe/H] to planet formation and the iron abundance in itself is used as a proxy to scale all elements. On the other hand, large surveys of stellar abundances show that this is not true. Here we use stellar abundances from the GALAH surveys to determine the average detailed abundances of Fe, Si, Mg, O, and C for a broad range of host star metallicities with [Fe/H] spanning from −0.4 to +0.4. Using an equilibrium chemical model that features the most important rock-forming compounds as well as volatile contributions of H2O, CO2, CH4, and CO, we calculate the chemical composition of solid planetary building blocks around stars with different metallicities. Solid building blocks that are formed entirely interior to the water ice line (T > 150 K) only show an increase in Mg2SiO4 and a decrease in MgSiO3 for increasing host star metallicity, which is related to the increase of [Mg/Si] for higher [Fe/H]. Solid planetary building blocks forming exterior to the water ice line (T < 150 K), on the other hand, show dramatic changes in their composition. In particular, the water ice content decreases from around ~50% at [Fe/H] = −0.4 to ~6% at [Fe/H] = 0.4 in our chemical model. This is mainly caused by the increasing C/O ratio with increasing [Fe/H], which binds most of the oxygen in gaseous CO and CO2, resulting in a small water ice fraction. Planet formation simulations coupled with the chemical model confirm these results by showing that the water ice content of super-Earths decreases with increasing host star metallicity due to the increased C/O ratio. This decrease of the water ice fraction has important consequences for planet formation, planetary composition, and the eventual habitability of planetary systems formed around these high-metallicity stars.
Published online 20 December 2019
Gesehen am 24.02.2020